Accomplishing Intergroup Relations in Group Homes: A Discursive Analysis of Professionals Talking About External and Internal Stakeholders - Saglietti, Marzia; Marino, Filomena (Frontiers in Psychology, 2022)
Focusing on one of the mostly studied dimensions of Social Psychology, i.e., intergroup relations, this article analyzes its discursively accomplishment in a specific group-based intervention, i.e., the talk and work of an Italian group home, i.e., a small alternative care facility hosting a group of out of home children. Particularly, we focus on the fictionally called “Nuns’ Home”, a group home previously investigated for its ethnocentric bias, and its intergroup relations with “inside” and “outside” groups – such as schools, biological families, social services. By combining a qualitative and quantitative approach in analyzing one audio-recorded ethnographic interview with the whole team of professionals, we aimed at accounting the multitude of internal and external stakeholders participants refer to; analyzing the discursive accomplishment of ingroup and outgroup in talk-in-interaction; investigating ingroup bias and group qualification. To do so, we detect social categorization markers and qualifying devices participants rely on when referring to groups. Results show that – amongst the numerous groups recognized – participants co-construct intergroup relations and ingroup bias implying negative assessment over external groups. Differently from traditional laboratory studies illustrating a substantial contraposition between ingroup and outgroup, our qualitative analysis reveals the multitude of groups by which the ingroup is formed – and their internal fragmentation. To conclude, we discuss the many implications of qualitatively studying intergroup relation in group homes and indicate future lines of research.